Intraoperative dexmedetomidine use associated with prolonged postanesthesia care unit recovery time after lung resection: a retrospective cohort study - Gao, Zhenglian; Jiang, Yan; Liu, Yixin; Yang, Chang; Zhang, Bangjian; Li, Ming (Frontiers in Pharmacology, 2025)
BackgroundDexmedetomidine, despite its wide-ranging benefits, may also pose a risk of delayed recovery in the postanesthesia care unit (PACU). Few studies have examined the relationship between dexmedetomidine and delayed recovery in the PACU after lung resection. Therefore, this retrospective cohort study aimed to investigate the effect of dexmedetomidine on PACU recovery time.MethodsThis study identified 1,397 eligible patients [dexmedetomidine-free (NO-DEX) group, n = 638; intraoperative dexmedetomidine use (DEX) group, n = 759] among 1,980 patients undergoing lung resection from January 2020 to December 2023. The primary outcome was the relationship between dexmedetomidine exposure and the risk of prolonged PACU recovery time; secondary outcomes were independent risk factors affecting PACU recovery time. The data were analyzed using propensity score matching and univariate and multivariate logistic regression analyses, as appropriate. In addition, we also developed a nomogram, which was evaluated using the calibration curve, receiver operating characteristic (ROC) curve, and decision curve analysis (DCA).ResultsAfter propensity score matching, there were 521 patients in each group. The incidence of PACU recovery time exceeding 60 min was 25.48%. Univariate logistic regression analysis showed that intraoperative dexmedetomidine use was associated with the risk of prolonged PACU recovery time [odds ratio (OR): 1.58; 95% confidence interval (CI): 1.18–2.11; p = 0.002]. Multivariate logistic regression analysis also showed a significant difference in the risk of prolonged PACU recovery time (OR: 1.60; 95% CI: 1.19–2.15; p = 0.002) between the NO-DEX and DEX groups. Sensitivity analyses under varying assumptions confirmed the robustness of our primary results. Independent risk factors for delayed recovery in the PACU included intraoperative dexmedetomidine use, advanced age, smoking, cardiovascular disease, and ASA physical status III, whereas regional block was associated with reduced risk. The predictive nomogram demonstrated moderate discrimination and estimated a 70% probability of delayed PACU recovery in patients presenting with all identified risk factors.ConclusionOur data demonstrated that intraoperative dexmedetomidine use was associated with prolonged PACU recovery time following lung resection, potentially increasing the pressure on busy recovery rooms.